The effect of green tea supplementation on obesity: A systematic review and dose–response meta‐analysis of randomized controlled trials - Lin, Ying; Shi, Dianfeng; Su, Bo; Wei, Jing; Găman, Mihnea‐Alexandru; Sedanur Macit, Melahat; Borges do Nascimento, Israel Júnior; Guimaraes, Nathalia Sernizon (Phytotherapy research, 2020)
The effects of green tea (GT) in obese subjects have been evaluated in different studies, but no consensus has been obtained due to the heterogeneity of the results. The dosage, the type of extract, and the duration of the intervention are the main contributors to the heterogeneity of the results. Therefore, the present systematic review and meta‐analysis aimed to evaluate the efficacy and dose–response relationship of GT. Several databases were searched from inception to September 2019 to identify clinical trials that examined the influence of GT supplements on obesity indices in humans. Combined results using the random‐effects model indicated that body weight (WMD: −1.78 kg, 95% CI: −2.80, −0.75, p = .001) and body mass index (BMI) (WMD: −0.65 kg/m2, 95% CI: −1.04, −0.25, p = .001) did change significantly following GT administration. The reduction in waist circumference (WC) after GT consumption was significant in subjects in trials employing GT ≥800 mg/day (WMD: −2.06 cm) and with a treatment duration <12 weeks (WMD: −2.39 cm). Following the dose–response evaluation, GT intake did alter body weight, with a more important reduction when the GT dosage was <500 mg/day and the treatment duration was of 12 weeks. The results of present meta‐analysis study support the use of GT for the improvement of obesity indices. Thus, we suggest that the use of GT can be combined with a balanced and healthy diet and regular physical exercise in the management of obese patients.